Hazor and the Battle of Joshua—Is Joshua 11 Wrong? - Yadin, Yigaʾel 1917-1984 (1976)
In his article "Hazor and The Battle of Deborah—Is Judges 4 Wrong?" BAR 01:04, Yohanan Aharoni writes (concerning the apparent endorsement by the BAR editor of my view that Judges 4 is "a late inaccurate gloss"): "Don’t reject the historicity of the Biblical text so easily".